HUBUNGAN PEMBERIAN INFORMASI PADA PASIEN RAWAT INAP TERHADAP KEPUASAN MUTU PELAYANAN DI UNIT ADMISI RSU SARAH MEDAN - Dyna Rakhelmi Rangkuti; Andini Mentari Tarigan; Juliana Hasibuan (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
The most frequent issues are those involving information and services, when patients feel that the hospital's offerings are inadequate, if not downright disappointing. When health services are able to satisfy their clients and live up to their expectations, they are considered to be of high quality. Patients' perceptions of the hospital's expectations and the caliber of its services affect how satisfied they feel. The goal of this study was to evaluate and pinpoint how Sarah General Hospital in Medan's admission unit informed inpatients about their satisfaction with the quality of the services they received. Cross sectional research methodology is used in this study. Purposive sampling was used to sample up to 88 responders from the population of this study, which included up to 718 patients. Chi-square test was utilized in data analysis along with univariate and bivariate analysis. The chi-square test analysis findings reveal that each variable's p-value comprises substantial proof (tangibles) obtained (0.002 <0.005), reliability with p-value (0.001 <0.005), responsiveness with p-value (0.000<0.005) empathy with p-value (0.009<0.005) and assurance with p-value (0.000<0.005). The availability of inpatient information and customer satisfaction with service quality in the admissions unit were related. The suggestion was hospitals should continue to enhance the quality of services connected to the service quality aspects, namely assurance and responsiveness.